2011
DOI: 10.2741/s152
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism in animals important roles in nutrition and health

Abstract: L-Tryptophan is a nutritionally essential amino acid for monogastric animals and preweaning ruminants because it cannot be synthesized in the body. Besides serving as a building block for proteins, tryptophan is a critical nutrient for the functions of nervous and immune systems. Over the past decades, much attention has been directed to study the role of tryptophan as a limiting amino acid in mammalian and avian nutrition. However, emerging evidence from recent studies shows that tryptophan and its metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…It has been described by Dr Barnes as the happy hormone2, involved in natural reward-related physiology and behaviour3, from feeding to sexual activity. Serotonin is biochemically derived from tryptophan and has various functions in different phyla, including both vertebrates and invertebrates, and plays a modulatory role in numerous physiological processes such as feed intake, reproduction, immunity and stress responses456.…”
mentioning
confidence: 99%
“…It has been described by Dr Barnes as the happy hormone2, involved in natural reward-related physiology and behaviour3, from feeding to sexual activity. Serotonin is biochemically derived from tryptophan and has various functions in different phyla, including both vertebrates and invertebrates, and plays a modulatory role in numerous physiological processes such as feed intake, reproduction, immunity and stress responses456.…”
mentioning
confidence: 99%
“…It was shown that these enzymatic activities could dampen T cell proliferation through nutrient deprivation (Cobbold et al, 2009). One of the many enzymes that were up-regulated was Tph-1 (tryptophan hydroxylase-1), a synthase which utilizes tryptophan as a substrate to produce serotonin and melatonin (Yao et al, 2011), and it was speculated that Tph-1 may precipitate the loss of tryptophan in the local microenvironment (Zelenika et al, 2001). In the present study, we sought to determine whether Tph-1, the isoform expressed in the periphery (Walther et al, 2003), could function as a regulator of immunity through the control of tryptophan metabolism and uncovered a novel and profound immunoregulatory function for this enzyme.…”
mentioning
confidence: 99%
“…Trp is an essential AA for human and animals and plays an important role in inflammatory regulation beyond building block for proteins synthesis [65]. The serious Trp concentration shows a highly inverse correlation with disease activity in IBD patients [66].…”
Section: Amino Acids: Application In Inflammatory Bowel Disease Thmentioning
confidence: 99%